Runoff suppression in freezing-thawing soils: The pivotal role of endemic bacterial inoculation - SADEGHI, SEYED HAMIDREZA; GHAREMAHMUDLI, SUDABEH (Journal of Soil and Water Conservation, 2026)
Soil and water loss, especially during freezing and thawing, is a major global issue, and bacteria, can serve as a practical biological approach to conserve soil and water resources. This study was designed to investigate the effects of endemic bacteria application on controlling runoff under freezing-thawing cycle conditions. Soil from the Badranlou Region in Iran was collected and transferred to small erosion plots. The most suitable endemic bacteria, identified from a soil microbank for soil and water conservation, were isolated, purified, proliferated, and inoculated onto the plots in six replicates with a 20% slope at the laboratory. Treatments—bacterial inoculation versus non-inoculation—were tested under a simulated single freezing–thawing cycle and 30 minute rainfall at about 70 mm h-¹. Results showed that, compared to the control, inoculation significantly reduced surface runoff volume and the runoff coefficient. After 60 days, inoculation increased the time to runoff by 102%, reduced runoff volume by 33%, extended the time to peak by 18%, and decreased the peak time by 83% (p